2010
DOI: 10.1542/peds.2009-1684
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Genetic Testing for Patients With Autism Spectrum Disorders

Abstract: BACKGROUND Multiple lines of evidence indicate a strong genetic contribution to autism spectrum disorders (ASDs). Current guidelines for clinical genetic testing recommend a G-banded karyotype to detect chromosomal abnormalities and fragile X DNA testing, but guidelines for chromosomal microarray analysis have not been established. PATIENTS AND METHODS A cohort of 933 patients received clinical genetic testing for a diagnosis of ASD between January 2006 and December 2008. Clinical genetic testing included G-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
256
4
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 356 publications
(287 citation statements)
references
References 40 publications
21
256
4
2
Order By: Relevance
“…Finally, although the common risk genes identified by our analysis are of limited clinical utility, more highly penetrant mutations although individually rare may be diagnostically significant across these neurodevelopmental disorders as is already being realised in ASDs. 29 …”
Section: Neuronal Cell Adhesion Genesmentioning
confidence: 99%
“…Finally, although the common risk genes identified by our analysis are of limited clinical utility, more highly penetrant mutations although individually rare may be diagnostically significant across these neurodevelopmental disorders as is already being realised in ASDs. 29 …”
Section: Neuronal Cell Adhesion Genesmentioning
confidence: 99%
“…The diagnostic yield of ASD genetic testing varies from 0.5% to 18%, depending on the type of testing. [7][8][9][10] Although genetic testing is now a standard of care and an integral part of evaluation of ASD, a genetic cause is identified in <25% of patients with ASD. 11 With the advancement of genomic technologies, another potential test-massively parallel sequencing (e.g., whole-exome and whole-genome sequencing analysis)-is gradually moving from the research laboratory to clinical settings for the identification of single genes associated with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Stobbe et al [9] collected 23 adult patients (range 18-45 years) with confirmed autism. CNVs were demonstrated in 9 of 23 (39.1%) of patients, compared with 18.2% in published pediatric cases of ASDs [10], which suggested that the adult ASD population is enriched for genomic imbalance and rare CNVs. Girirajan et al identified recurrent CNVs, including DPP10, PLCB1, TRPM1, NRXN1, FHIT, and HYDIN, that are enriched in autism by focusing on gene-disruptive events.…”
Section: Rare Copy Number Variants In Asdmentioning
confidence: 91%